Inhibiting Amikacin Resistance in Multidrug-Resistant Bacteria with Cadmium and Pyrithione - Angel J. Magaña; David Ngo; Kenneth Burgos; Carolina Dominguez Maldonado; Omniya Abdelmaksoud; Jan Sklenicka; Tung Tran; Fernando Pasteran; Verónica Jimenez; María S. Ramirez; Marcelo E. Tolmasky (Current Microbiology, 2025)
The ongoing antibiotic resistance crisis is one of the most pressing public health challenges. Multidrug-resistant bacterial pathogens are reaching the point where some are becoming untreatable. Consequently, besides discovering novel antibiotics, alternative strategies must be explored to manage the problem. One approach is developing inhibitors that overcome resistance to antibiotics currently in use. Resistance to aminoglycosides such as amikacin is mainly due to aminoglycoside-modifying enzymes. Despite being refractory to most resistance enzymes, the semisynthetic amikacin is inactivated by aminoglycoside 6′- N -acetyltransferases type I [AAC(6′)-I], of which AAC(6′)-Ib is the most common in Gram-negative pathogens. The discovery that certain divalent and monovalent cations interfere with enzymatic acetylation catalyzed by AAC(6′)-Ib opens possibilities for developing formulations combining antibiotics with these cations to enhance efficacy. Addition of CdCl₂ to in vitro enzymatic assays inhibited transfer of an acetyl group to the 6′- N position of amikacin, kanamycin, and tobramycin. Hence, Cd 2 ⁺ is a potential adjuvant to aminoglycosides for treating AAC(6′)-Ib-mediated resistant infections. It was initially disappointing that, as with other divalent cations, CdCl₂ addition to cultures of bacteria harboring AAC(6′)-Ib did not reverse resistance. However, the inhibitory action of Cd 2 ⁺ became evident when combined with the ionophore pyrithione. The complex efficiently inhibited resistance in Acinetobacter baumann ii and Klebsiella pneumoniae harboring AAC(6′)-Ib. Furthermore, the combination inhibited amikacin resistance in carbapenem-resistant K. pneumoniae clinical isolates. These results add another cation to the arsenal of potential aminoglycoside adjuvants, which could be developed alone or in coordination complexes with ionophores to treat multidrug-resistant infections.